Penyimpangan Pelaksanaan Undang-Undang Nomor 40 Tahun 2007 dalam Pendirian Perseroan Terbatas - Putri, Astuti Yudhika; Santoso, Budi (Fakultas Syariah INSURI Ponorogo, 2023)
The establishment of a limited liability company has its own conditions which have been regulated in law number 40 of 2007 regarding Limited Liability Companies, however, when someone is about to set up a company limited, there are some who deviate from the law that has been determined wrong one of which is the requirement for the establishment of a PT to be carried out by (2) two or more people, however, this is not regulated in the PT Law clearly regarding the requirements to become a shareholder so that in practice it often occurs irregularities where the use of shareholders nominee. Agreement nominee as a shareholder in PT is an agreement and or a statement confirming that share ownership in the limited liability company for and on behalf of another person. The Company Law does not regulate provisions the use of nominee shareholders so that it can trigger legal problems if shareholders nominee it is not in good faith